JUAL BELI MURABAHAH PERSPEKTIF REGULASI DAN PRAKTIK DI LEMBAGA KEUANGAN SYARIAH - Muhamad Izazi Nurjaman; Doli Witro; Sofian Al Hakim (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
One of the financing instruments developed by Islamic Financial Institutions (LKS) is the murabahah contract. Murabahah financing is a contract that dominates the financing process compared to other contracts. Various regulations support murabahah financing operations in LKS, such as the Fatwa of the National Sharia Council of the Indonesian Ulama Council (DSN-MUI), the Circular Letter of the Financial Services Authority, Law Number 21 of 2008 concerning Islamic Banking and various other regulations. The number of regulations that usually regulate always found multiple problems. One of them is the overlapping regulations that make a regulated object confusing policy implementers and the public. This study aims to explain the position of the murabahah contract based on the regulations that govern it to strengthen the statement of the murabahah contract in Islamic Financial Institutions. This article is legal research that uses a juridical-normative approach. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the analysis show that there are various regulations governing murabahah financing. The substance of the regulation refers to the fiqh muamalah maliyyah, which was transformed into the Fatwa of the MUI DSN. From these various regulations, there is a harmonization of regulations that are mutually complementary to each other, according to their functions. This is an indication of the harmonization that occurs between Indonesian Sharia Bank (BSI) regulations.